2021
DOI: 10.1007/s10461-021-03349-y
|View full text |Cite
|
Sign up to set email alerts
|

Telehealth for HIV Care Services in South Carolina: Utilization, Barriers, and Promotion Strategies During the COVID-19 Pandemic

Abstract: To ensure continuing HIV care services during the COVID-19 pandemic, telehealth has been recommended and implemented in numerous HIV-related facilities. This study aims to understand telehealth utilization for HIV care services in South Carolina (SC), identify barriers to telehealth during COVID-19, and investigate strategies to facilitate remote HIV care delivery. In-depth interviews with 11 management personnel from 8 HIV-related facilities in SC were analyzed using thematic analysis. Utilizations of telehea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
36
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(52 citation statements)
references
References 33 publications
6
36
0
2
Order By: Relevance
“…Our findings align with prior research that has shown how the COVID-19 pandemic created barriers to treatment and care services because of the inability of in-person medical visits, staffing disruptions, and fewer blood tests and lab results [ 29 31 ]. Additionally, patients have also reported dissatisfaction with online and virtual telemedicine, including needing longer lead time and planning for medical appointments [ 30 ].…”
Section: Discussionsupporting
confidence: 88%
“…Our findings align with prior research that has shown how the COVID-19 pandemic created barriers to treatment and care services because of the inability of in-person medical visits, staffing disruptions, and fewer blood tests and lab results [ 29 31 ]. Additionally, patients have also reported dissatisfaction with online and virtual telemedicine, including needing longer lead time and planning for medical appointments [ 30 ].…”
Section: Discussionsupporting
confidence: 88%
“…In response to the need for increased social distancing, HIV clinics implemented telehealth options for visit completion or postponed visits ( Budak et al, 2021 , Ridgway et al, 2020 ). While traditionally, “telehealth” has implied video visits accessed over the internet, and therefore has required access to smartphones or computers and the internet, during the pandemic, many HIV clinics offered telephone-only telehealth visits, or made other accomodations, such as providing patients with smartphones, in order to reduce the impact of these barriers ( Auchus et al, 2021 , Brody et al, 2021 , Budak et al, 2021 , Dandachi et al, 2020 , Yelverton et al, 2021 ). In many cases ( Auchus et al, 2021 , Brody et al, 2021 , Coppock et al, 2021 , El-Nahal et al, 2021 , Mayer et al, 2020 ), but not all ( Fadul, 2020 , Quiros-Roldan et al, 2020 ), offering visits via telehealth appears to have been successful at keeping people engaged in care at pre-pandemic levels, at least in the short term.…”
Section: Discussionmentioning
confidence: 99%
“…We focused our investigation on demographics (based on well-documented racial and ethnic disparities in HIV care outcomes), social determinants of health, substance use, mental health symptoms and treatment, and the impact of the COVID-19 pandemic. Many HIV clinics adapted care models quickly to allow patients to engage in care without requiring in-person visits (e.g., offering telehealth and telephone visits) ( Brody et al, 2021 , Yelverton et al, 2021 ). Prior research has suggested that visit completion during the pandemic was similar or better than during the pre-pandemic period ( El-Nahal et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Also, general and administrative costs for laboratories are relatively fixed and do not increase dramatically as testing volume increases. The COVID-19 pandemic showed the potential of remote care services to support regular screening for HIV and other STIs remotely when the capacity to have in-person visits for screening decreased 16–19 . This experience illustrated that developing and sustaining channels of laboratory testing that are robust to external barriers to testing—be they pandemic, 20 travel distances, 4,21 or concerns about attending testing sites due to stigma and medical mistrust 22,23 —represent a high value proposition for governments.…”
Section: Budgeting and Costsmentioning
confidence: 99%